THE INFLUENCE OF LIQUIDITY RATIO, LEVERAGE, PROFITABILITY ACTIVITIES ON PROFIT GROWTH OF FOOD AND BEVERAGE COMPANIES IN THE INDONESIA STOCK EXCHANGE - Harismawati Nur Hidayah; Herlambang Pudjo Santosa (Institute of Computer Science (IOCS), 2022)
Profit growth is a ratio that shows the company's ability to increase net profit compared to the previous year. The purpose of the company is to get a profit. This study aims to examine and analyze the effect of working capital to total assets, debt to asset ratio, total asset turnover, and net profit margin on profit growth in Food and Beverage sector companies listed on the Indonesia Stock Exchange in 2018-2020. Determination of the sample in this study is purposive sampling with sampling in accordance with certain criteria. The sample used in this study is the Food and Beverage sector companies listed on the Indonesia Stock Exchange in 2018-2020. The analytical method used in this research is multiple regression analysis. Hypothesis testing is done by using the F test (simultaneous test) and t test (partial test). The results of this study indicate that working capital to total assets and total asset turnover do not contribute to the profit growth of Food and Beverage sector companies listed on the Indonesia Stock Exchange, and debt to asset ratios and net profit margins contribute to the profit growth of Food and Beverage sector companies. Beverage listed on the Indonesia Stock Exchange.